PERKAWINAN JANDA TANPA AKTA CERAI (Studi Kasus pada Masyarakat Kecamatan Lengayang Kabupaten Pesisir Selatan) - Januardi, Hengki; Efrinaldi, Efrinaldi; Efrinaldi, Efrinaldi (UIN Imam Bonjol Padang, 2020)
He problem in the widow's marriage without a divorce certificate was a marriage carried out by a widow at the Office of Religious Affairs without a divorce certificate from the Religious Court, and the Office of Religious Affairs recorded the marriage. This type of research is field research using the sociological approach of Islamic law. The results revealed several findings about the factors causing widow marriages without divorce certificates from the Religious Courts, namely: (1) factors that cause widow marriage without divorce certificates are economic factors, widow desire factors for marriage and lack of public legal awareness of marriage. The legal consequence is that the marriage can be canceled (Article 22 of Law No. 1 of 1974). Children remain joint responsibility and shared assets can be divided between husband and wife (2) widow's marriage procedure without divorce certificate in accordance with the positive law stipulated in KMA No. 477 of 2004 jo. KMA No. 298 of 2003. However, the KUA married it with an attachment to the divorce statement from Wali Nagari as a requirement for marital administration. (3) The KUA's consideration in carrying out widow marriage registration without divorce certificate was that the widow had divorced and arrived in the period the marriage is already complete in the Shari'a. If the marriage is not carried out, it will have a negative impact on both parties such as adultery and public gossip